The Revived from Oblivion: Struggling for Historical Memory of the 110th Kalmyk Cavalry Division. Part 2 - Utash B. Ochirov (Oriental Studies, 2021)
Introduction. The article aims to analyze the historiography and history of the 110th Kalmyk Cavalry Division, the only ethnic military unit (largely staffed by Kalmyks) that fought at the front during the Great Patriotic War. While the division is worthy of memory and respect for its contribution to the battle against the enemy, its history was surrounded with defamatory myths that have nothing in common with real events. Granted the disappearance of most of the Division’s documents handed over to the archives, it has taken several decades to objectively study its history. Materials and methods. Besides the historical-genetic method, which was the principal one for the present research, historical-systemic and historical-comparative methods were used. The sources were books and articles, office documentation and correspondence from various archival repositories, personal correspondence and memoirs of the veterans of the 110th Kalmyk Cavalry Division, as well as of the researchers of its history. Results. The article is a consistent examination of the historiography of the subject; this may be divided into five stages designated in the article as i) a period of silence and lies (1943–1957), ii) a period of ‘sporadic’ searches (1957–1967), iii) a period of active scientific work (1967–1977), iv) a period of indifference (1977–2011), and v) a period of new scholarly interest in the subject (2011–present). The Kalmyk Cavalry Division has long been an object of defamatory insinuations and calumny when it was accused of ”unreliability”, denounced as ”a gang” or even as German collaborators; these had clearly political implications. Meanwhile, the study of the history of the Division was seriously complicated by the loss of most of its documents although after its disbandment these were handed over according to the inventory along with the banners. Also, this interfered with the process of preserving the historical memory of the only ethnic formation that fought against the enemy during the Great Patriotic War. Hence, the difficulty that the scholars in the field have had to overcome was immense. The second part of the article describes the forth and fifth stages. Conclusions. The historiography associated with the studies of the history of the Kalmyk Cavalry Division may be described as a difficult and winding path, with periods of both indifference and activation that had to be overcome. However, in the course of a long struggle, justice was restored, and the historical memory of the Kalmyk Division was returned to the people.